Design of a Customer Service System Based on Video Conference Using WebRTC - Fathana, Adhitya; Piarsa, I Nyoman; Buana, Putu Wira (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol 12 No 3 (2024): Vol. 12, No. 3, December 2024, 2024)
Technological developments have changed the way customer service operates, from face-to-face interactions to more efficient digital platforms. WebRTC is emerging as a key technology in building video conferencing-based customer service systems for real-time communication and enhanced customer experience. This research focuses on developing a video conferencing system with WebRTC, through the stages of design, implementation, and testing. The results of this research show that testing on Microsoft Edge provides a total inspection time of 14,629 ms with 584.1 MB memory usage and 4.4% CPU. Meanwhile, on Google Chrome, the total inspection time was recorded at 14,845 ms with memory usage of 656.1 MB and CPU of 0.8%.  The results show an efficient use of resources.